2022
DOI: 10.3390/jof8070667
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of a New Calcium/Calmodulin-Dependent Protein Kinase (CaMK1) in the Citrus Pathogenic Fungus Penicillium italicum

Abstract: Calcium (Ca2+)/calmodulin-dependent protein kinases (CaMKs) act as a class of crucial elements in Ca2+-signal transduction pathways that regulate fungal growth, sporulation, virulence, and environmental stress tolerance. However, little is known about the function of such protein kinase in phytopathogenic Penicillium species. In the present study, a new CaMK gene from the citrus pathogenic fungus P. italicum, designated PiCaMK1, was cloned and functionally characterized by gene knockout and transcriptome analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that this pathway can play a role in cell cycle control in S . cerevisiae and other organisms [ 89 ], with a function at the G 2 /M checkpoint [ 90 92 ]. In C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that this pathway can play a role in cell cycle control in S . cerevisiae and other organisms [ 89 ], with a function at the G 2 /M checkpoint [ 90 92 ]. In C .…”
Section: Resultsmentioning
confidence: 99%
“…This gene encodes a calmodulin-dependent kinase (CaMK) and serves as an effector of the calcium-calcineurin signaling pathway, an important component of fungal stress responses [86][87][88]. Previous studies have shown that this pathway can play a role in cell cycle control in S. cerevisiae and other organisms [89], with a function at the G 2 /M checkpoint [90][91][92]. In C. neoformans, loss of CMK1 may inhibit the mutant from the appropriate stress-induced cell cycle arrest, leading to increased growth in the presence of the cellular stress.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Fungal growth, sporulation, virulence, and stress tolerance are regulated through Ca 2+ -involved cross-linking mechanisms, including DNA replication and damage repair, cell cycle and nuclear division, and MAPK signaling. In Penicillium italicum, gene knockout and complementation analysis indicated the requirement of the PiCaMK1 in the fungal vegetative growth, sporulation, full virulence, and responses to salt (salinity) and mannitol (osmotic) stresses [50]. Additionally, in this group, although less represented, is argininosuccinate lyase (PDIP_06990).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Li and co-workers [4] analyzed Calcium (Ca2+)/calmodulin-dependent protein kinases (CaMKs), identifying a new gene in P. italicum (PiCaMK1). Results obtained in this work suggest that PiCaMK1 function involves the regulation of multiple physical and cellular processes of this pathogen, including growth, conidiation, virulence, and environmental stress tolerance.…”
mentioning
confidence: 99%